2015
DOI: 10.1177/0091450915579875
|View full text |Cite
|
Sign up to set email alerts
|

Public Health and Alcohol Licensing in the UK

Abstract: This article discusses the role of public health in alcohol licensing in the UK, with a particular focus on the implementation of national legislation and guidance in local regulatory environments. It identifies a number of practical and theoretical challenges through an analysis of historical trends in licensing practice, recent policy developments, and key licensing decisions and appeals. There are strong historical precedents for a focus on strategic harm reduction in UK licensing; however, because licensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Notwithstanding successes in some areas [20], many were surprised at how little impact health evidence had in the licensing arena. This illustrates the persistence, or perhaps re-emergence, of the idea of an ideal-type model of “ evidence-based policymaking ” [34] which proposes that there “ can and should be a direct and unproblematic link between ‘the evidence’ and policy decisions and outcomes ” [50] (p. 2). In contrast, evidence from policy theory suggests that policy is neither solely nor directly based on scientific evidence, nor should it be [50,51], and this study suggests that licensing policy, as a political process, is no different.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notwithstanding successes in some areas [20], many were surprised at how little impact health evidence had in the licensing arena. This illustrates the persistence, or perhaps re-emergence, of the idea of an ideal-type model of “ evidence-based policymaking ” [34] which proposes that there “ can and should be a direct and unproblematic link between ‘the evidence’ and policy decisions and outcomes ” [50] (p. 2). In contrast, evidence from policy theory suggests that policy is neither solely nor directly based on scientific evidence, nor should it be [50,51], and this study suggests that licensing policy, as a political process, is no different.…”
Section: Discussionmentioning
confidence: 99%
“…Licensing has historically had a strategic focus on the public good but health considerations, and particularly long-term health, have had little traction in day to day licensing [34]. An earlier study of the Licensing (Scotland) Act 2005 found that the public health objective of licensing was not well understood and fit poorly within a paradigm traditionally focused on harms at the level of individual licensed premises rather than the population harms of concern to public health [41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations